Age and surgical outcome of low‐grade glioma in Sweden. (13th June 2018) - Corell, A.; Carstam, L.; Smits, A.; Henriksson, R.; Jakola, A. S.
Abstract : Background: Low‐grade gliomas (LGG) are slow‐growing primary brain tumors that typically affect young adults. Advanced age is widely recognized as a poor prognostic factor in LGG. The impact of age on postoperative outcome in this patient group has not been systemically studied. Methods: We performed a nationwide register‐based study with data from the Swedish Brain Tumor Registry (SBTR) for all adults diagnosed with a supratentorial LGG (WHO grade II astrocytoma, oligoastrocytoma, or oligodendroglioma) during 2005‐2015. Patient‐ and tumor‐related characteristics, postoperative complications, and survival were compared between three different age groups (18‐39 years, 40‐59 years, and ≥60 years). Results: We identified 548 patients; 204 patients (37.2%) aged 18‐39 years, 227 patients (41.4%) aged 40‐59 years, and 117 patients (21.4%) ≥60 years of age. Unfavorable preoperative prognostic factors (eg, functional status and neurological deficit) were more common with increased age ( P < .001). In addition, overall survival was significantly impaired in those 60 years and above ( P < .001). We observed a clear dose‐response for age with separation of survival curves at 50 years. Biopsy was more common in patients ≥60 years ( P < .001). Subgroup analysis of patients with resection revealed a higher amount of postoperative neurological deficits in older patients ( P = .029). Conclusion: In general, older patients with LGG have several unfavorable prognostic factors compared with younger patients but seem to tolerate surgery in a comparable fashion. However, more neurological deficits were observed following resections in elderly. Our data further support a cutoff at 50 years rather than 40 years for selection of high‐risk patients.